Improving PAI Learning Outcomes with The Theme "Let's Pray" Through The Cooperative Method of Make a Match Model in Class 4 Students Of SDN Bandar Kidul 2 Kota Kediri - Robi'ah, Siti; Zunairoh, Yuyun; Ahid, Nur (Proceeding International Conference on Education, 2023)
PAI learning currently focuses more on developing abilities and information processing rather than simply absorbing information. Learners need to increase their activity through exercises or small group assignments and explaining ideas to others. PAI is a study material with abstract objects built through deductive reasoning, where the truth of a concept is obtained as a logical result of previous truths. This research aims to determine the improvement in PAI learning outcomes by applying the Make A Match model cooperative learning method to grade 4 students at SDN Bandar Kidul 2, Kediri City. This research uses an action research method consisting of three rounds. The research results show that the Make A Match model cooperative learning method can improve PAI learning outcomes and motivate students to learn .